The manufacturing–services dynamic in economic development. (21st September 2016) - KUCERA, David; RONCOLATO, Leanne
Abstract: This article addresses the debate on services‐led growth in which services are variously portrayed as a substitute for or as a leading or lagging complement to manufacturing. Following a survey of related empirical studies, it applies growth decomposition methods to data for 18 countries in Asia and Latin America for 1980–2005, focusing on manufacturing and services that make intensive use of information and communication technology. By grouping the countries into four categories according to aggregate labour productivity and employment growth, the authors seek to identify common structural characteristics of better and worse performing countries. They also consider the viability of the services‐led growth path in India in particular.